Application of Phase-Selective Organogelators (PSOGs) for Marine Oil Spill Remediation - Huifang Bi; Chunjiang An; Catherine N. Mulligan; Zhi Chen; Kenneth Lee; Jiyuan Wen; Zhaonian Qu; Xinya Chen (Journal of Marine Science and Engineering, 2022)
Oil spill incidents frequently cause serious impacts on the ecosystem, society, and economy. To cope with this problem, the use of phase-selective organogelators (PSOGs) has been developed in recent years as a promising oil spill response tool, which can congeal oils from biphasic systems, accelerating oil removal and recovery and reducing impacts on the environment. This article systematically reviews reported technologies for the use of PSOGs for potential oil spill remediation in the literature from January 2016 to May 2022. It discusses several kinds of PSOGs based on molecular structures which are possible for gelling oil in the presence of water/seawater. Their mechanisms for phase-selective gelation are summarized, including hydrogen bonding, π–π stacking interactions, van der Waals force, hydrophobic interactions, etc. The currently possible deployment methods for the application of PSOGs are explored; carrier solvents and powder form are frequently used. Moreover, the challenges and the corresponding recommendations regarding standardized testing protocols and evaluation framework, gelation selectivity, as well as challenges in field tests, are further discussed.